Impaired Cerebral Autoregulation and Vasomotor Reactivity in Sporadic Alzheimer’s Disease - S.S. Meel-van den Abeelen, Aisha; Lagro, Joep; H.E.A. van Beek, Arenda; A.H.R. Claassen, Jurgen (Current Alzheimer Research, 2014)
Background Understanding the relationship between vascular disease and Alzheimer’s disease (AD) will enhance our insight into this disease and pave the way for novel therapeutic research. Cerebrovascular dysfunction, expressed as impaired cerebral autoregulation and cerebral vasomotor reactivity, has been observed in transgenic mouse models for AD. Translation to human AD is limited and conflicting however. Objective To investigate if impaired cerebral autoregulation and cerebral vasomotor reactivity, found in animal models for AD, are present in human sporadic AD. Methods In 12 patients with mild to moderate AD (75 SD 4 yr) and 24 controls matched for age and history of hypertension, all without diabetes, we measured blood pressure (Finapres) and cerebral blood flow-velocity (transcranial Doppler). Cerebral autoregulation was assessed during changes in blood pressure induced by single and repeated sit-stand maneuvers. Cerebral vasomotor reactivity was assessed during hyperventilation and inhalation of 5 % carbon dioxide. Results During single sit-stands, controls had a 4% (SD 8) decrease in cerebrovascular resistance during a reduction in blood pressure, and an 8 % (SD 11) increase during a rise in blood pressure, indicating normal cerebral autoregulation. These changes were not seen in AD (p=0.04). During repeated sit-stands, blood pressure fluctuated by 20 % of baseline. This led to larger fluctuations in cerebral blood flow in AD (27 (6) %) than in controls (22 (6) %, p < 0.05). Cerebral vasomotor reactivity to hypercapnia was reduced in AD (42.7 % increase in CBFV, versus 79.5 % in controls, p = 0.03). Conclusion Observations of impaired cerebrovascular function (impaired autoregulation and vasoreactivity) in transgenic mouse models for AD were confirmed in patients with sporadic AD.
Keywords: cerebral amyloid angiopathy